Vitamin D Supplementation Compared With Inhalation Therapy In Asthma Patients: A Meta-Analysis Using Revman - Alifah Raihan Fadilla; Imran Safei; Abdul Mubdi Ardiansar Arifuddin Karim (International Medical Journal Corp. Ltd, 2025)
Introduction: Asthma is a chronic inflammatory disease of the airways that remains difficult to control despite the availability of standard therapies such as inhaled corticosteroids (ICS). The role of vitamin D as an immunomodulator with anti-inflammatory properties has attracted attention as a potential adjunctive therapy. Several studies have reported an association between vitamin D deficiency and increased asthma severity. This study aims to compare the effectiveness of vitamin D supplementation and inhalation therapy in controlling asthma symptoms. Methods: This meta-analysis was conducted in accordance with PRISMA guidelines. A systematic search was performed in PubMed, EMBASE, Cochrane Library, and ClinicalTrials.gov. Included studies were randomized controlled trials (RCTs) evaluating the effect of either vitamin D supplementation or inhalation therapy on the Asthma Control Test (ACT) score. Data were analyzed using a random-effects model in Review Manager 5.2, with effect sizes presented as Standardized Mean Differences (SMD). Results: A total of 11 studies were included (6 on vitamin D, 5 on inhalation therapy). Vitamin D supplementation showed a pooled SMD of 0.54 (95% CI: 0.25–0.84; p = 0.0003), indicating a moderate effect, with high heterogeneity (I² = 93%). Studies by Tuba Çiftçi (2019) and Rubén Andújar-Espinosa (2020) reported large effects (SMD > 1), while Adrian (2015) showed no significant effect. Inhalation therapy produced more variable outcomes; Belachew (2022) showed the largest effect (SMD = 1.32), while studies such as Boonsawat (2015) and Kondla (2016) reported small or nonsignificant effects. Overall, vitamin D showed a more consistent and generally greater effect compared to inhalation therapy. Conclusion: Vitamin D supplementation appears to be an effective adjunctive therapy for improving asthma control, particularly in patients with vitamin D deficiency. Further large-scale RCTs are needed to determine optimal dosing, duration, and the most responsive patient subgroups.